Biofungicidas e fungicidas qúimicos no manejo de doenças na cultura da soja - Santos, Dhylan Keillor Queiróz dos (2023)
Soybean (Glycine max (L.) Merril) is one of the most significant crops globally. However, its productivity is compromised by foliar diseases throughout its growth stages. The genera Bacillus spp. and Trichoderma spp. represent the majority of formulated biological control agents for disease management, owing to their efficacy in the field and other relevant factors. Nevertheless, the combination of Bacillus spp. and Trichoderma spp. with chemical fungicides and even with each other requires further investigation for foliar disease control in soybean. Thus, this study examined the influence of products formulated with Trichoderma sp. and Bacillus sp. on foliar disease management in soybean and assessed the compatibility between biological agents and chemical products. In the field, the effectiveness of applications of Bacillus sp.-based products (Ba), Trichoderma sp.-based products (Tr), systemic fungicides (S), and multisite (M) fungicides, along with their combinations (+) or successions (-) (Ba-S; Tr-S; Tr+Ba; Tr+Ba-S; Tr-Ba-S; S+M), was tested for foliar pathogen control over two consecutive years. Ba-S demonstrated effectiveness in reducing the severity of Asian rust, while Tr-Ba-S exhibited target spot mitigation properties; both were effective in reducing brown spot manifestation. Ba, S+M, Ba-S, and Tr-Ba-S productivity was 25% higher, and leaf defoliation was reduced by 20% compared to the control. Furthermore, pathogen incidence was significantly reduced in seeds from Ba, Ba-S, and Tr-Ba-S treatments. Compatibility between Bacillus sp. and Trichoderma sp.-based products, as well as with chemical fungicides, was tested in a chamber application on Petri plates. Compatibility tests showed that Trichoderma spp. compounds reduced the growth of Bacillus spp., while Bacillus spp. compounds did not reduce the growth of Trichoderma spp. Only mancozeb and carboxamide + strobilurin reduced the growth of Trichoderma spp. Additionally, compounds produced by Trichoderma spp. and Bacillus spp. reduced the growth of the pathogens Septoria glycines, Corynespora cassiicola, and Cercospora sojina. Thus, products based on Bacillus spp. and Trichoderma spp. are effective against soybean phytopathogens, but combining these agents is not the optimal management strategy for foliar diseases. Instead, using only Bacillus spp. with or without prior application of Trichoderma spp. on crop residues, followed by systemic products, represents the best management practice, leading to increased productivity, disease reduction, and avoiding interference of compounds with bacterial growth.